Caracterização do exsudato de sementes de Moringa oleífera Lamarck e investigação de seu papel na defesa do vegetal. - Sousa, Antônio Juscelino Sudário (2013)
Moringa oleifera (moringa) is a species belonging to the family Moringaceae which is characterized as having high resistance to insects and fungi. Previous work carried out by our research group revealed the presence of chitin-binding proteins in moringa seeds, among them Mo-CBP3, suggesting a positive correlation between this protein and the plant resistance. At the onset of the new plant development, for germination to occur, seed imbibition is required, a process followed by exudation. In exudation process, primary and secondary metabolites are released in the medium outside the seeds, some of them protecting the new plant against herbivores and/or pathogens. This study aimed to characterize the chemical composition and biological activities of moringa seed exudate and to investigate the presence of Mo-CBP3 in the exudate, in order to contribute to the establishment of its physiological role. Initially, the best conditions for exudation were established, emphasizing the time and solvent. A higher exudation of seed proteins was observed in distilled water after 24 hours. This exudate showed the presence of activities related to primary (protease, β-1,3- glucanase, chitinase, trypsin inhibitor and papain inhibitor) and secondary (steroid and saponins) metabolites. Mo-CBP3 was also detected in the exudate, using polyclonal antibodies anti-Mo-CBP3. The presence of Mo-CBP3 in the moringa seed exudate was confirmed after chromatography on chitin matrix and analyses by dot blotting and polyacrylamide gel electrophoresis. The data obtained showed that the retained material on the chitin matrix corresponds to 0.26% of the total protein, it is recognized by anti-Mo-CBP3 and has electrophoretic profile similar to that of Mo- CBP3 which was purified from moringa seeds. In the activity tests to pathogens, the seed exudate showed no antifungal activity, under the conditions used, except for Candida parapsilosis which had a slight reduction in its growth rate. In contrast, a potent activity against nematode was found as the seed exudate was able to cause a mortality rate up to 100% of Meloidogyne incognita in J2 stage. When investigated the presence of Mo-CBP3 in moringa hoots, a plant organ that shows the exudation phenomen and is also able to interact directly with the nematode, positive results were found. In fact, Mo-CBP3 is present in moringa hoots, in the initial stages of the plant development, according to the results shown by ELISA and RT-PCR. The data, taken together, suggest that in the exudation phenomen, proteins must play essential roles. In the case of moringa, Mo-CBP3 already participates in the initial stages of development of this tree species, playing a role that must be related to protection against pathogens.